Bottom‐up Generation of Miniaturized Coaxial Double Electrodes with Tunable Porosity. Issue 12 (6th July 2015) - Karajić, Aleksandar; Reculusa, Stéphane; Heim, Matthias; Garrigue, Patrick; Ravaine, Serge; Mano, Nicolas; Kuhn, Alexander
<x xml:space="preserve">Abstract</x> A bottom‐up approach is proposed for the design of a fully integrated miniaturized electrochemical cell with independently addressable cylindrical macroporous electrodes. The presented strategy allows excellent control over the pore size, the thickness of each macroporous electrode, as well as their separation gap. Such coaxial architectures are potentially suitable for the elaboration of miniaturized electrochemical devices such as (bio)fuel cells, supercapacitors, or biosensors.